2012
DOI: 10.1021/nn203917d
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Reinforcement of Polymer-Based Nanocomposites by Graphene

Abstract: The stress transfer between the internal layers of multilayer graphene within polymer-based nanocomposites has been investigated from the stress-induced shifts of the 2D Raman band. This has been undertaken through the study of the deformation of an ideal composite system where the graphene flakes were placed upon the surface of a polymer beam and then coated with an epoxy polymer. It is found that the rate of band shift per unit strain for a monolayer graphene flake is virtually independent of whether it has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
237
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 269 publications
(266 citation statements)
references
References 53 publications
(142 reference statements)
19
237
3
1
Order By: Relevance
“…It was observed that a crack initiates at the graphene-matrix interface in both cases. This corresponds to the observation by Gong et al [8] that the adhesion between graphene and polymer is relatively poor. Then crack grows throughout the whole interface region and propagates into the matrix, they deflect on the nanosheets.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It was observed that a crack initiates at the graphene-matrix interface in both cases. This corresponds to the observation by Gong et al [8] that the adhesion between graphene and polymer is relatively poor. Then crack grows throughout the whole interface region and propagates into the matrix, they deflect on the nanosheets.…”
Section: Discussionsupporting
confidence: 90%
“…Novoselov, Young and their colleagues at the University Manchester [42][43][44] studied the change in the strain distribution on graphene, and observed that the strain across the flake is uniform at the applied strain up to 0.6%. After that cracks form in polymer coating layers, with the graphene remaining intact.…”
Section: Properties Of Graphene/polymer Interface: Inverse Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Perfect graphene has extremely high strength ~ 130 GPa and a modulus of ~ 1 TPa [1,2]. These properties make graphene a material with potential for use in the polymer industry, such as in future graphene-reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…These properties make graphene a material with potential for use in the polymer industry, such as in future graphene-reinforced composites. Measurable and satisfactory strengthening effects can be achieved by encapsulating graphene sheets (up to two layers) between layers of the polymer [1]. For graphene electronic applications, it is important to establish a relationship between the electrical properties and the material stress state.…”
Section: Introductionmentioning
confidence: 99%